COVID dan Budaya Pedagang Pasar Tradisional di Makassar - Muhammad Arsyad Rahman; Muhammad Basir; Yahya Yahya (Universitas Hamzanwadi, 2023)
COVID is a disease from a medical point of view, while COVID as a disease associated with causes is a cultural study. The objective of this research is to explore the knowledge, beliefs, norms, habits, values, experiences, and fatalistic attitudes of traders in traditional markets that can influence traders' behavior in COVID-19 prevention in the traditional market of Power, Makassar. Ethnography becomes this method of research, and it observes traders in their surroundings. The results of the research showed that knowledge traders could not recognize the characteristics of people exposed to COVID except for symptoms of cough and fever, and COVID is a common but deadly disease. From the point of view of belief, COVID-19 originates from God and the cause-and-effect relationship between human beings and the environment, as well as human actions. From the point of view of the norm, there are sanctions, both for the discipline and prevention of COVID-19, and traders adhere to the old norms. Experienced aspects of disease prevention in the past are more real, and experiences during pandemics are more abstract. The culture of traders in social life is a diachronic and synchronous combination of the relationship between COVID-19, traditional markets, and public health.